Impact of normal weight obesity on fundamental motor skills in pre-school children aged 3 to 6 years - Musalek, Martin; Kokstejn, Jakub; Papez, Pavel; Scheffler, Christiane; Mumm, Rebekka; Czernitzki, Anna-Franziska; Koziel, Slawomir (Anthropologischer Anzeiger; Bericht uber die biologisch-anthropologische Literatur, 2017)
Normal weight obesity is defined as having excessive body fat, but normal BMI. Even though previous research revealed that excessive body fat in children inhibited their physical activity and decreased motor performance, there has been only little evidence about motor performance of normal weight obese children. This study aims to establish whether normal weight obese pre-school children aged 3-6 years will have a significantly worse level of fundamental motor skills compared to normal weight non-obese counterparts. The research sample consisted of 152 pre-schoolers selected from a specific district of Prague, the Czech Republic. According to values from four skinfolds: triceps, subscapula, suprailiaca, calf, and BMI three categories of children aged 3-6 years were determined: A) normal weight obese n = 51; B) normal weight non-obese n = 52; C) overweight and obese n = 49. The Movement Assessment Battery for Children (MABC-2) was used for the assessment of fundamental motor skills. Normal weight obese children had significantly higher amount of adipose tissue p < 0.001 than normal weight non-obese children but the same average BMI. Moreover, normal weight obese children did not have significantly less amount of subcutaneous fat on triceps and calf compared to their overweight and obese peers. In majority of MABC-2 tests, normal weight obese pre-schoolers showed the poorest performance. Moreover, normal weight obese children had significantly worse total standard score = 38.82 compared to normal weight non-obese peers = 52.27; p < 0.05. In addition, normal weight obese children had a more than three times higher frequency OR = 3.69 CI95% (1.10; 12.35) of severe motor deficit performance ≤ 5th centile of the MABC-2 norm. These findings are strongly alarming since indices like BMI are not able to identify normal weight obese individual. We recommend verifying real portion of normal weight obese children as they are probably in higher risk of health and motor problems than overweight and obese population due to their low lean mass.
Keywords: obezita; tuková tkáň; pohybová aktivita; Humans; index tělesné hmotnosti; Body Mass Index; dítě; Child; lidé; předškolní dítě; Czech Republic; motorické dovednosti; Obesity; Motor Activity; Body Weight; tělesná hmotnost; Česká republika; Motor Skills; Child, Preschool; Adipose Tissue